The Impact of Time Series-based Interruption Cost on Online Risk Assessment in Distribution Networks - Leite, Jonatas Boas [UNESP] (2016)
Recent transformations in design, planning and operation of distribution system represent the needed evolutionary step toward a modern integrated infrastructure where new risk based operations balance economic and reliability criteria. Risk assessment tools are useful for monitoring and supervisory control because they provide operators with the capability to quantify the tradeoff between reliability and economic performance. One part of the risk assessment is the determination of financial impact that can be expressed through the total cost of energy supply interruption. The calculation of interruption cost is typically associated with planning assessment where several parameters essential to network operation are neglected. The proposed mathematical model incorporates time-dependent interruption events, and integrates the spatio temporal risk data using a GIS platform.